Tanggung Jawab Negara terhadap Tidak Terpenuhinya Keterwakilan Perempuan dalam Pemilihan Umum dalam Perspektif Obligation of Conduct - Al Maidah Putri (Jurnal Hukum Lex Generalis, 2025)
The state is responsible for fulfilling women’s representation through the obligation of conduct, which means not only creating regulations that support gender equality but also actively and effectively implementing these policies. The state must create conditions that enable women to participate equally in politics. Although women’s quotas in the legislature have been implemented, women’s representation in elections remains low. The obligation of conduct perspective emphasizes the importance of the state’s role in fulfilling human rights, particularly women’s political rights, by creating an environment that genuinely and sustainably supports participation and gender equality.